EFFECT OF PART-TIME PATCHING THERAPY ON VISUAL OUTCOME IN PATIENTS WITH ANISOMETROPIC AMBLYOPIA VISITING AFIO RAWALPINDI - Ashraf, Ammarah; Masud, Hannan; Rabbani, Shafaq; Noor, Palwasha (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the effect of amblyopia patching therapy on visual outcome in young and adults at 6th and 12th week.Study Design: Quasi-experimental study.Place and Duration of Study: Armed Forces Institute of Ophthalmology Rawalpindi, Pakistan, from Sep 2018 to Jan 2020.Methodology: Out of 110, follow up was successfully completed by 91 eyes. Subjects were divided into young and adult based on age. Age ranging from 5-12 years included in the young group and adult group included those ranging from 13-20 years. Anisometropic amblyopia was considered. Amblyopia due to any other disease were excluded. Subjects were advised patching therapy daily for 4 hours in the affected eye. Follow up was 3 weekly for 12 weeks and the effect of patching therapy was assessed by visual improvement. Statistical analysis was done with SPSS version 21.Result: Out of 91 eyes with amblyopia, 51 (56.6%) were included in the young group while 40 (43.4%) were included in the adult group. In the young group, visual improvement was seen in 40 (78.4%) while in the adult group 24 (60%) showed improvement in vision. Mean visual improvement in young was 1.66 ± 1.099 while 1.03 ± 0.944 in the adult group. Maximum visual improvement in both groups was seen till the 6th week of patching.Conclusion: Patching therapy is effective even at later ages too. However, continuing patching for more than 6 weeks doesn’t show much improvement in vision.